2013
DOI: 10.5897/ajmr12.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ascorbic acid, citric acid, lactic acid, NaCl, potassium sorbate and Thymus vulgaris extract on Staphylococcus aureus and Escherichia coli

Abstract: Staphylococcus aureus and some strains of Escherichia coli are frequently implicated in foodborne diseases. This study examined the effects of some compounds (ascorbic acid, citric acid, lactic acid, sodium chloride, potassium sorbate and Thymus vulgaris extract) on growth of S. aureus and E. coli. Lactic acid (0.03% or 0.1%) alone nearly completely inhibited growth of S. aureus or E. coli, respectively. Citric acid (0.03%) reduced growth and ascorbic acid (0.1%) nearly completely inhibited the growth of S. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…have been reported by El-Gebaly et al [31]. On the contrary, other studies [30,[32][33][34] have found that ascorbic acid did not inhibit the growth of E. coli and P. aeruginosa but made them more resistant to antimicrobials and physical disinfection.…”
Section: Discussionmentioning
confidence: 89%
“…have been reported by El-Gebaly et al [31]. On the contrary, other studies [30,[32][33][34] have found that ascorbic acid did not inhibit the growth of E. coli and P. aeruginosa but made them more resistant to antimicrobials and physical disinfection.…”
Section: Discussionmentioning
confidence: 89%
“…Dental implant failure can be the consequence of the host-to-implant tissue response, or of peri-implant microbial infection [ 20 , 23 , 27 , 28 , 29 , 30 ]. Osteoblast maturation and epithelial sealing can be fostered by several implant topography features [ 20 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA at low pH is able to freely cross the microbial membrane, and once inside the cytoplasm, it dissociates into CA anions and protons, leading to the acidification of the intracellular media—thus causing functional and structural damage to the bacteria [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Like EDTA, SCDT acts as a metal chelator inhibiting biofilm formation . Although the other excipients in Pulmicort, such as NaCl, citric acid, and Tween 80, have all been shown to influence bacterial growth independently in other research, none of them had any effect on bacterial growth in our study. This is most likely secondary to the low concentrations used.…”
Section: Discussionmentioning
confidence: 99%